Physicochemical properties of tamarind and pineapple fruit pulps and powders - Mokhtar, Taufiq Aminullah; Yusof, Yus Aniza; Chin, Nyuk Ling; Othman, Siti Hajar; Serikbaeva, Asya Demeukhanovna; Aziz, Mohammad Gulzarul (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
Tamarind and pineapple fruit pulps and powders were assessed based on their physicochemical properties such as crude protein, crude fibre, fat, ash, moisture content, water activity (Aw), particle shape, particle size distribution, and density. Both of the fruit powders were subjected to a similar spray-drying process with the addition of 10% w/v of maltodextrin. The nutritional value in terms of crude protein (0.33 - 0.60%), moisture content (4.80% - 25.31%), crude fiber (16.92 - 79.92%), and fat (0.40 - 0.63%) for both fruit pulp and powders shows a significant difference at p<0.05. Therefore the fruit powders can be developed and improved for further processing into tablets.